A subset of group A-like var genes encodes the malaria parasite ligands for binding to human brain endothelial cells - Claessens, Antoine (2013)
Cerebral malaria is the most deadly manifestation of infection with Plasmodium falciparum. The pathology of cerebral malaria is characterized by the accumulation of infected erythrocytes (IEs) in the microvasculature of the brain caused by parasite adhesins on the surface of IEs binding to human receptors on microvascular endothelial cells. The parasite and host molecules involved in this interaction are unknown. We selected three P. falciparum strains (HB3, 3D7, and IT/FCR3) for binding to a human brain endothelial cell line (HBEC-5i). The whole transcriptome of isogenic pairs of selected and unselected parasites was analyzed using a variant surface antigen-supplemented microarray chip. After selection, the most highly and consistently up-regulated genes were a subset of group A-like var genes (HB3var3, 3D7_PFD0020c, ITvar7, and ITvar19) that showed 11- to >100-fold increased transcription levels. These var genes encode P. falciparum erythrocyte membrane protein (PfEMP)1 variants with distinct N-terminal domain types (domain cassette 8 or domain cassette 13). Antibodies to HB3var3 and PFD0020c recognized the surface of live IEs and blocked binding to HBEC-5i, thereby confirming the adhesive function of these variants. The clinical in vivo relevance of the HBEC-selected parasites was supported by significantly higher surface recognition of HBEC-selected parasites compared with unselected parasites by antibodies from young African children suffering cerebral malaria (Mann–Whitney test, P = 0.029) but not by antibodies from controls with uncomplicated malaria (Mann–Whitney test, P = 0.58). This work describes a binding phenotype for virulence-associated group A P. falciparum erythrocyte membrane protein 1 variants and identifies targets for interventions to treat or prevent cerebral malaria.